ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI MINYAK VCO INDUSTRI KECIL WAIPIAH COCONUT DI KEC. TNS KAB. MALUKU TENGAH - Penina T. Istia; Hendriette D. Titaley; Nelda Maelissa (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
Central Maluku is an agrarian area which has an abundance of agricultural commodities, especially the plantation sub-sector which is a trading activity in Maluku. one of the sub-sectors is coconut plantations. Coconut (CocosNucifera) is a plantation crop that is widespread in almost all regions of Indonesia. Generally, coconut plants are produced into copra which will later be used as raw materials in making coconut cooking oil. The great potential of coconut in the Sub-District of TNS (TeonNilaSerua), opens opportunities for its citizens to develop small businesses in the middle of processing virgin coconut oil (VCO). In fact, VCO produced by the community in Layeni village, Jerili village and Yafila village, is able to penetrate the consumer market even though the VCO oil production results are not widely known and known by the people of Maluku as a whole about the benefits and benefits of CVO oil produced by small business groups in TNS area.VCO production results are not too well known by consumers in the area of order.